2004
DOI: 10.1111/j.0953-816x.2004.03458.x
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala central nucleus function is necessary for learning but not expression of conditioned visual orienting

Abstract: When exposed to pairings of a visual stimulus with food delivery, rats normally acquire both conditioned orienting responses directed toward the visual stimulus and conditioned food-related responses. Consistent with the results of previous lesion studies, reversible inactivation of amygdala central nucleus function before each conditioning session prevented the acquisition of conditioned orienting responses, whereas food-related behaviors were acquired normally. By contrast, neither inactivation nor neurotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 40 publications
(68 reference statements)
4
63
1
Order By: Relevance
“…The CN has strong projections to the hypothalamus, reticular formation, and brainstem nuclei, and so it is often argued to be involved in the arousal of behavioral, autonomic, and endocrine responses (Cardinal et al, 2002). This is consistent with other reports that CN lesions produce deficits in attentional tasks (Holland et al, 2000(Holland et al, , 2001McDannald et al, 2004), CS processing or associability (Holland and Gallagher, 1993a,b), and tasks that have assessed arousal (Merali et al, 1998;Wilhelmi et al, 2001).…”
Section: The Role Of the Amygdala In Instrumental Conditioningsupporting
confidence: 82%
“…The CN has strong projections to the hypothalamus, reticular formation, and brainstem nuclei, and so it is often argued to be involved in the arousal of behavioral, autonomic, and endocrine responses (Cardinal et al, 2002). This is consistent with other reports that CN lesions produce deficits in attentional tasks (Holland et al, 2000(Holland et al, , 2001McDannald et al, 2004), CS processing or associability (Holland and Gallagher, 1993a,b), and tasks that have assessed arousal (Merali et al, 1998;Wilhelmi et al, 2001).…”
Section: The Role Of the Amygdala In Instrumental Conditioningsupporting
confidence: 82%
“…In the same study, the authors showed that the medial CeA cells retrogradely labeled from the SNc expressed an immediate-early gene, FOS, after conditioned orienting responses, demonstrating the direct involvement of the CeA to SNc projection in conditioned orienting. Furthermore, a series of studies demonstrated time dependencies such as those observed by Holland and Gallagher (2006): CeA function was critical only at the time of acquisition (McDannald et al, 2004;Groshek et al, 2005), and function of another brain region, the dorsal lateral striatum, was critical only at the time of expression of that learned response (Han et al, 1997). Most important, SNc function was critical to both the acquisition and expression of that behavior (El Almamy and Holland, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…Within this system, the OFC and BLA are well-positioned to integrate contextrelevant multi-modal sensory input from sensory cortices with reward-related information from other mesocorticolimbic brain regions in order to guide goal-directed behaviors (Brog et al, 1993;Carmichael and Price, 1995b;Fuchs et al, 2008;McDannald et al, 2004;Price, 1986;Sah et al, 2003;Xie et al, 2010). For instance, in addition to dopaminergic input from the VTA to the OFC and BLA, glutamatergic inputs from the OFC and BLA and dopaminergic input from the VTA converge on dendritic spines of nucleus accumbens (NAc) medium spiny neurons (Kelley et al, 1982;Bouyer et al, 1984;Haber et al, 1995).…”
Section: Discussionmentioning
confidence: 99%